Post‐treatment clinical course following botulinum toxin injection therapy for adductor spasmodic dysphonia: Analysis of data from a placebo‐controlled, randomized, double‐blinded clinical trial in Japan. Issue 5 (28th September 2021) - Hirose, Kahori; Asano, Kento; Sakaguchi, Masahiko; Nagao, Asuka; Nakahira, Maya; Doi, Nao; Kobayashi, Taisuke; Hyodo, Masamitsu
Abstract: Objective: Botulinum toxin (BT) therapy is a first‐line treatment for spasmodic dysphonia (SD). However, a detailed chronological course and clinical factors that affect the therapeutic effect have been vague. In this study, we analyzed the data from our placebo‐controlled, randomized, double‐blinded parallel‐group comparison/open‐label clinical trial of BT (Botox) to clarify these. Methods: A total of 22 patients with abductor SD (ADSD) were enrolled. The female‐to‐male ratio was 20:2 with a mean age of 40.0 ± 10.3 years and a median duration of symptoms of 7.5 years. The therapeutic effect was evaluated based on the change in the number of aberrant morae (phonemes), GRBAS scale, Voice Handicap Index (VHI), and Visual Analogue Scale (VAS). Results: The change in the number of aberrant morae peaked at 2 weeks and lasted for 12 weeks in the BT group with significance ( P < .01) compared to the placebo group. Objective improvement (number of aberrant morae and [S] element in GRBAS) preceded subjective improvement (VHI and VAS). The change in number of aberrant morae and VHI showed a significant correlation ( P < .01). The changes in the number of aberrant morae, VHI, and VAS in younger subjects were greater than in older subjects. Patients who presented with post‐treatment breathy hoarseness or dysphagia showed better therapeutic effects. Conclusions: BT therapy was effective for ADSD based on both objective and subjective assessments. Improvements in subjective parameters were delayed compared to objective measures due to post‐treatment breathy hoarseness. However, this adverse event was believed to reflect the treatment effect. Level of Evidence: 1b. Abstract : Comparisons of post‐treatment change values between subjects with and without adverse events (AEs). Change values of number of aberrant morae, (S) in GRBAS, Voice Handicap Index and Visual analogue scale were greater in subjects with AEs than those without AEs.